Importance of benzoyltransferase GcnE and lysine benzoylation of alcohol dehydrogenase AdhB in pathogenesis and aflatoxin production in Aspergillus flavus - Xuan Chen; Lihan Wu; Yuqi Zhang; Sen Wang; Shihua Wang (mBio)
ABSTRACT Lysine benzoylation (Kbz) is a newly identified post-translational modification associated with active transcription and metabolism in eukaryotes. However, whether Kbz exists in pathogenic fungi and its function remains unknown. Here, we demonstrated for the first time that Kbz is present in Aspergillus flavus and identified 60 benzoylated sites on 46 benzoylated proteins by global benzoylome analysis. Our data demonstrated that alcohol dehydrogenase B (AdhB) is regulated by benzoylation on lysine 321 (K321), and mutations of Kbz site in AdhB significantly reduced the alcohol dehydrogenase activity in vivo and in vitro. Both adhB deletion mutant and benzoylated site mutants (K321R and K321A) exhibited similar phenotype, including decreased conidiation and seed colonization, increased sclerotia formation and aflatoxin production, and more sensitive to cell wall damage stress. We also found that GcnE has benzoyltransferase activity in vitro and in vivo, and its repression leads to decreased Kbz level and enzymatic activity of AdhB. The catalytic site E139 is important for the benzoyltransferase function of GcnE. Our study uncovers a previously unknown mechanism by which benzoylation regulates AdhB activity to affect the development, secondary metabolism, pathogenicity, and stress response of A. flavus. Meanwhile, it points out the important role of Kbz in the pathogenicity of pathogenic fungi.IMPORTANCEAspergillus flavus is a ubiquitous opportunistic pathogen of plants and animals, which produces carcinogenic and toxic secondary metabolite aflatoxin. A. flavus and aflatoxin contamination have emerged as a global food safety concern. Currently, post-translational modification plays crucial modulatory roles in the fungal development and virulence, but the role of benzoylation in fungal pathogenicity remains undetermined, which limits the development of prevention and control technique. Here, we first identified 46 benzoylated proteins in A. flavus, and found that benzoyltransferase GcnE exerted effects on pathogenicity and aflatoxin production by regulating the benzoylation of AdhB. This finding not only provided valuable information for prevention and control of A. flavus contamination, but also offered basic knowledge for investigation of the regulation mechanism of secondary metabolism in other fungi.